Bilateral Internal Mammary Artery Bypass Grafting: Sternal Wound Infection in High-Risk Population. Should Sternal Infection Scare Us?. (20th July 2018) - Ravaux, Justine Mafalda; Guennaoui, Thami; Mélot, Christian; Schraverus, Peter
Background: Bilateral internal mammary arteries (BIMAs) remain underused in coronary artery bypass grafting (CABG), especially in elderly, diabetic, and obese patients. This study investigated incidence of sternal wound infection (SWI), sternal instability (SI), and reintervention for bleeding (RIB) in this high-risk population. Methods: A single-center retrospective observational study was performed in "Grand Hôpital de Charleroi, Gilly, Belgium." A total of 319 patients undergoing CABG from December 2011 to December 2015 were included. Three main outcome measures (SWI, SI, and RIB) were investigated in obese vs nonobese, diabetic vs nondiabetic, and elderly vs younger patients. Results: In all, 14 SWI, 11 SI, and 6 RIB were discounted. Death rate was as follows: SWI: 2/14 vs 17/305 ( P = .178), SI: 2/11 vs 17/308 ( P = .081), and RIB: 2/6 vs 17/313 ( P = .004). In obese (n = 113) vs nonobese (n = 206) patients, there was no difference for SWI ( P = .263), SI ( P = .565), and RIB ( P = .332). In diabetic (n = 118) vs nondiabetic (n = 201) patients, there was no difference for SWI ( P = .642), SI ( P = .497), and RIB ( P = .298). In elderly (n = 62) vs younger (n = 257) patients, there was no difference for SWI ( P = .619), SI ( P = .915), and RIB ( P = .385). Conclusions: Obesity, age, and diabetes treated by insulin (or not) do not seem to be risk factors for developing SWI, SI, or RIB in patients receiving a CABG using BIMA. Nevertheless, mortality was higher in RIB group.